Педагогічні умови національно-патріотичного виховання дітей старшого дошкільного віку у спільній роботі сім’ї та ЗДО - Григорук, Любов Анатоліївна (My University, 2023)
У роботі представлено результати дослідження проблеми національно- патріотичного виховання дітей старшого дошкільного віку у спільній роботі сім’ї та закладу дошкільної освіти. Проаналізовано стан розробки проблеми національно-патріотичного виховання у психолого-педагогічній літературі. З’ясовано особливості та зміст національно-патріотичного виховання дітей старшого дошкільного віку у закладі дошкільної освіти та в сім’ї. Наведено результати дослідницької роботи з вивчення рівня національно-патріотичної вихованості дітей старшого дошкільного віку та визначення педагогічних умов і методичних рекомендацій щодо спільної роботи сім’ї та закладу дошкільної освіти у процесі національно-патріотичного виховання дітей старшого дошкільного віку.
The paper presents the results of the study of the problem of national-patriotic upbringing of older preschool children in the joint work of the family and the preschool education institution. The state of development of the problem of national- patriotic education in psychological and pedagogical literature is analyzed. The peculiarities and content of national-patriotic upbringing of older preschool children in a preschool education institution and in the family have been clarified. The results of the research work on the study of the level of national-patriotic education of older preschool children and the determination of pedagogical conditions and methodical recommendations regarding the joint work of the family and the preschool education institution in the process of national-patriotic education of older preschool children are given. Keywords: national-patriotic education, patriotism, older preschool age, pedagogical conditions, optimization of the educational process, interaction between educators and parents.
Keywords: національно-патріотичне виховання; патріотизм; старший дошкільний вік; педагогічні умови; взаємодія вихователів і батьків; оптимізація виховного процесу